DEVELOPMENT OF ENTREPRENEURIAL AND ETHICS-BASED CREATIVE ECONOMY INDUSTRIES THAT HAVE GLOBAL COMPETITIVENESS - Hakim, Alif Lukmanul (Jurnal Education and Development, 2025)
This study aims to discuss the ways and forms of increasing the creative industry in the production and marketing of modern Indonesian batik that can be globally competitive. The research method used in this study is a qualitative research method that takes data and information from batik producer business actors in Yogyakarta. This study found that there are six way (Design Innovation and Product Diversification, Technology Utilization in Production Process, Improving the Quality of Human Resources, Marketing and Branding, Increasing Access to International Markets, Certification and Recognition of Works) and three forms (Developing Product Quality, Increase Product Variants ,Contemporary and Flexible Design) of increasing the creative economy industry through the production of modern Indonesian batik. In addition, the main point in increasing the potential of the creative economy industry through production is to improve the upstream area first, namely by creating creative and innovative designs so that with contemporary designs it will be more easily accepted by the national and international markets. Besides issuing various motif designs and providing a touch of deep philosophical meaning, another factor is creating product variants that are needed by the market, so that this flexibility will expand the existing audience both on a national and international scale.